1988
DOI: 10.1111/j.1365-246x.1988.tb01143.x
|View full text |Cite
|
Sign up to set email alerts
|

3-D numerical modelling of the conductive heat flow of SW England

Abstract: The effect of 3-D geology on conductive heat flow was investigated using the finite element technique on two models from SW England, one a regional model centred on the Comubian batholith as a whole and the other a more detailed model centred on the Cammenellis pluton. Only two rock types, granite and country rock, were used to represent the geology of the region and yet good agreement between modelled and observed data was obtained provided that the granite was assumed to be highly homogeneous, with surface h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…9b), a 10 km thick layer of granite is buried beneath 200m of basement. This depth is consistent with gravity and thermal models (Edwards 1984a;Sams & Thomas-Betts 1988). Basement, with the same physical properties as in the non-granite model, constitutes the rest of the crust.…”
Section: Possible Crustal Modelssupporting
confidence: 83%
See 1 more Smart Citation
“…9b), a 10 km thick layer of granite is buried beneath 200m of basement. This depth is consistent with gravity and thermal models (Edwards 1984a;Sams & Thomas-Betts 1988). Basement, with the same physical properties as in the non-granite model, constitutes the rest of the crust.…”
Section: Possible Crustal Modelssupporting
confidence: 83%
“…1). This adamellitic granite batholith is thought to be of crustal origin (Shackleton, Ries & Coward 1982), and to have a depth extent from 10 to 15 km and an average width of about 30km (Edwards 1984a;Sams & Thomas-Betts 1988). A prominent, 20-30mgal low in gravity coincides with the outcrop of granite on land, and the anomaly's southwestward extension more than 200 km out to sea indicates that the batholith's buried length is at least of that order.…”
Section: Introduction a N D Geological Backgroundmentioning
confidence: 96%
“…The regional geometry of the batholith has been examined by gravity modelling (WillisRichards 1986;Sams & Thomas-Betts 1988). These studies, combined with a few conclusions that can be drawn from seismic experiments, support the idea of the granite being homogeneous down to a fiat base.…”
Section: Introductionmentioning
confidence: 85%
“…The Cornubian batholith is characterized by the highest measured heat flow values in the UK. The heat flow field and subsurface temperatures for the Carnmenellis granite are discussed by Wheildon & Rollin (1986), Lee (1986) and by Sams & Thomas-Betts (1988). The predicted sub-surface temperature profile for the Carnmenellis granite provides a temperature of 200°C at about 5.4km and indicates a temperature of 370 deg C at a depth of 10 km.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that heat flow refraction played a significant role due to the complex 3D form of the batholith. This suggestion was later assessed by Sams and Thomas-Betts (1988) who performed 3D numerical modelling of the heat flow field in the SW. The study confirmed that the surface heat flow pattern is dominated by the 3D form of the batholith with heat refraction due to thermal conductivity contrasts enhancing heat flow in the granite and lateral flow of heat caused by heat production contrasts diminishing it.…”
Section: Introductionmentioning
confidence: 99%